Bypassing a Separated Instrument in Mandibular First Premolar with Two Canals – A Case Report - Mohd Nazrin Isa; Aws Hashim Ali AL-Kadhim (UITM, 2024)
Journal of Health and Clinical Sciences Vol 6 Issue 2 Page (52-56)